Relative Movements of Domains in Large Molecules of the Immune System - Wolfgang Schreiner; Rudolf Karch; Reiner Ribarics; Michael Cibena; Nevena Ilieva (Journal of Immunology Research)
Molecular dynamics was used to simulate large molecules of the immune system (major histocompatibility complex class I, presented epitope, T-cell receptor, and a CD8 coreceptor.) To characterize the relative orientation and movements of domains local coordinate systems (based on principal component analysis) were generated and directional cosines and Euler angles were computed. As a most interesting result, we found that the presence of the coreceptor seems to influence the dynamics within the protein complex, in particular the relative movements of the two α-helices, Gα1 and Gα2.